Microchilus dressleri, a new name for Microchilus campanensis Kolan. (Orchidaceae) - Kolanowska, Marta (Phytotaxa, 2015)
A large number of studies on the Neotropical orchid genus Microchilus Presl (1827: 94) resulted in over 130 new specific epithets within this taxon since 2002 (eg. Ormerod 2002, 2005, 2007, 2008, 2009, 2013). The name of a new species described in 2014 based on material collected in Panama was identical with the previously published Microchilus campanensis Ormerod (2009: 120). A new name for Microchilus campanensis Kolanowska (2014: 185) is hereby proposed.